2007
DOI: 10.1007/s00464-007-9311-z
|View full text |Cite
|
Sign up to set email alerts
|

Influence of instrument size on endoscopic task performance in pediatric intracorporeal knot tying

Abstract: Endoscopic knot tying was performed faster in the neonatal simulator box using pediatric needle-holders while maintaining knot quality. Upper limb muscular recruitment was reduced resulting in less discomfort for the surgeon.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
16
0

Year Published

2008
2008
2017
2017

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 21 publications
(16 citation statements)
references
References 18 publications
(26 reference statements)
0
16
0
Order By: Relevance
“…Currently, there is very little literature examining the use of simulation in PLS, with only 4 citations identified using the following search terms: pediatric, laparoscopy, surgery, and simulators [10][11][12][13]. The first article by Lasko et al [10] examined the use of these simulators in pediatric training programs via a North American survey of trainees and program directors.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Currently, there is very little literature examining the use of simulation in PLS, with only 4 citations identified using the following search terms: pediatric, laparoscopy, surgery, and simulators [10][11][12][13]. The first article by Lasko et al [10] examined the use of these simulators in pediatric training programs via a North American survey of trainees and program directors.…”
Section: Discussionmentioning
confidence: 99%
“…They found that their modular training program significantly improved the efficiency and speed of performing the tasks in the group with less MAS experience while having little impact upon the more experienced group. The fourth and final article by Lee et al [13] used a neonatal simulator to assess the influence of instrument size on performing pediatric intracorporeal knot tying. They asked a group of pediatric surgeons to perform the knot tying with adult and pediatric needle holders.…”
Section: Discussionmentioning
confidence: 99%
“…These studies searched for proper operating surface height and monitor position, optimal optical axis-to-target view angles, appropriate manipulation angles and proper intra-corporal/extra-corporal instrument length ratio (17)(18)(19). In addition, other studies have discussed the impact of a poor ergonomic set-up during procedures on the physical discomfort that the surgeons experience (20)(21)(22)(23). However, the integration of the insights from different studies into one ergonomic skills simulator is still missing.…”
Section: Introductionmentioning
confidence: 94%
“…Thus, there is an increased importance of visualizing instruments at all times while within the patient’s body. [47]…”
Section: Current Limitations and Considerations Of Mismentioning
confidence: 99%